The chemistry of the pedoderm – part 2: Dichrostachys cinerea patches and adjacent grassland in the southern Kruger National Park, South Africa. Issue 4 (2nd October 2022) - Mills, Anthony J; Strydom, Tercia; Allen, Jessica L
Abstract : The small tree, Dichrostachys cinerea, occurs in dense patches within grasslands on gabbro-derived soils in the southern Kruger National Park. It is not known whether soil properties in the grasslands affect tree establishment. As a first step in identifying soil properties potentially underpinning differences in vegetation structure, we analysed the soil chemistry of the pedoderm (0–2 cm) in Dichrostachys patches and adjacent open grassland. Relative to the Dichrostachys patches, the pedoderm of the grassland was significantly richer in K (1.4-fold), Ca (2.6-fold), Mg (3.4-fold), Mn (1.7-fold), B (1.2-fold) and Na (1.6-fold). The pH of the grassland was also higher than in the Dichrostachys patches (6.45 ± 0.14 vs 5.53 ± 0.09). It is unlikely that the vigour of tree seedlings, tree ramets or grasses in the Dichrostachys patches would be constrained by the concentrations of K, Ca, Mg, Mn, B and Na, or the pH, at the study site. Greater concentrations of K, Ca, Mg, Mn, B and Na in the pedoderm of the grassland are, however, likely to be linked to relatively greater nutritive value of the grass sward and in turn greater herbivory pressure. This effect is a potential cause of the greater constraint of D. cinerea seedlings and/or ramets in the grassland than in the Dichrostachys patches.